IMPROVING THE FOREIGN POLICY OF RUSSIA ON THE BASIS OF THE GRAVITY MODELING (ON THE EXAMPLE OF THE BRICS) - E. A. Degtereva; Yu. N. Moseikin; V. Yu. Chernova (Модернизация, инновация, развитие, 2017)
The article investigates the features of construction of gravity models, the results of the use of which will allow to identify eff ective ways of Russian foreign policy improvements.Purpose of the article: multigravitatsion development model of Russia's foreign trade, which will identify forward the development of export-import relations in the framework of inter-regional trade area of the Russian Federation, including integration associations such as the EU, BRICS, CIS.Methodology: methodological basis of the study make up scientific methods of cognition, namely, methods of theoretical generalization and comparison; method of integrated and structural analysis.Results: During the studied analyzed Russia's foreign trade turnover, the results of which revealed that for the country's economic development is important as a variety of trade fl ows and capital fl ows, which in turn updates the problem of formation and development of the national foreign trade potential, finding the optimal proportion of commodity structure diversification and the introduction of eff ective mechanisms of regulation of export-import operations. The solution of the problem determined the conduct of the study articles Russian contemporary maps of foreign cooperation in the conditions of existing sanctions and embargoes, as well as the identification of targeted country markets for Russia's non-oil exports with a separate allocation problem area that emerged as a result of external challenges of political and economic nature faced by Russia because of the military confl ict in Ukraine. Special attention is paid to the distribution of Russian imports by partner countries.Significance: the example of EU integration associations of the CIS and the BRICS, which make up multiregional commercial space of Russia, multigravitatsionnaya model is constructed in order to assess the impact of Russia's cooperation with the EU member countries, CIS countries and the BRICS, as well as to forecast and analyze trade fl ows as the country as a whole, and in the context of export and import.